Efficacy of Recombinant Human-Soluble Thrombomodulin for Severe Acute Pancreatitis in a Rat Experimental Model. Issue 4 (April 2020) - Matsumoto, Masataka; Kamei, Keiko; Chikugo, Takaaki; Matsumoto, Ippei; Kawaguchi, Kohei; Takeyama, Yoshifumi
Abstract : Objectives: Early death in severe acute pancreatitis (SAP) is caused by pancreatic necrosis and multiple-organ failure due to microcirculation disorder. The aim of this study was to prove that recombinant human-soluble thrombomodulin (rTM) has therapeutic effects on SAP by preventing pancreatic necrosis and organ failure. Methods: Male Wister rats were used. Cerulein was administered intraperitoneally 4 times every 1 hour, and lipopolysaccharide was administered intraperitoneally 3 hours after. One hour after administration of lipopolysaccharide, rTM was injected intravenously. Rats were observed for 24 hours after starting the experiment, and the survival rate was evaluated. All surviving rats were killed, and the blood sample, liver, and pancreas were excised. Serum amylase, aspartate aminotransferase, alanine aminotransferase, and high mobility group box 1 were measured, and the liver and pancreas were examined histologically. For the evaluation of microcirculation, von Willebrand factor staining was performed. Results: S erum amylase, aspartate aminotransferase, and alanine aminotransferase were significantly decreased. The survival rate was significantly improved to 100%. Moreover, serum high mobility group box 1 was decreased. Liver injury and pancreatic necrosis became less severe, and microcirculation was preserved histologically. Conclusions: Early administration of rTM prevents organ failure by maintenance of microcirculation and improves prognoses of SAP.